28.1k views
2 votes
Which statement explains why the solution to the equation is x=4

Which statement explains why the solution to the equation is x=4-example-1
User Xkeshav
by
4.6k points

1 Answer

2 votes

Answer:

C. The
x-value of 4 produces the same
y-value in both
f(x) = (x-2)^(3)-6 and
g(x) = \sqrt[3]{x+4}.

Explanation:

Let
f(x) = (x-2)^(3)-6 and
g(x) = \sqrt[3]{x+4}. A value of
x is a solution of the formula if and only if
f(x) = g(x). If we know that
x = 4, then values of each function are, respectively:


f(x) = (x-2)^(3)-6


f(4) = 2^(3)-6


f(4) = 2


g(x) = \sqrt[3]{x+4}


g(4) = \sqrt[3]{8}


g(4) = 2

Since
f(4) = g(4), then
x = 4 is a solution of
(x-2)^(3)-6 = \sqrt[3]{x+4}. Hence, correct answer is C.

User Zef
by
5.0k points